2017
DOI: 10.1128/jvi.01820-16
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of Koala Retrovirus within a Wild Koala Population

Abstract: Koala populations are in serious decline across many areas of mainland Australia, with infectious disease a contributing factor. Koala retrovirus (KoRV) is a gammaretrovirus present in most wild koala populations and captive colonies. Five subtypes of KoRV (A to E) have been identified based on amino acid sequence divergence in a hypervariable region of the receptor binding domain of the envelope protein. However, analysis of viral genetic diversity has been conducted primarily on KoRV in captive koalas housed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(120 citation statements)
references
References 32 publications
(78 reference statements)
11
105
4
Order By: Relevance
“…Pseudomapping of the sequence reads to the KoRV A genome (complete gag, pro-pol and env genes) and type sequences of the hypervariable region of the env gene (base pairs 6000-6575 of KoRV A) of each of the previously identified KoRV subtypes (KoRV A to I as per the classification scheme used in Chappell et.al. 2016 21 ) demonstrated that while QLD koalas had multiple subtypes within individuals, SA animals had far lower KoRV subtype diversity. Significantly different expression was observed for KoRV A,B,D,E and G variants between QLD and SA samples (unpaired t-test with unequal variance, P<0.05) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomapping of the sequence reads to the KoRV A genome (complete gag, pro-pol and env genes) and type sequences of the hypervariable region of the env gene (base pairs 6000-6575 of KoRV A) of each of the previously identified KoRV subtypes (KoRV A to I as per the classification scheme used in Chappell et.al. 2016 21 ) demonstrated that while QLD koalas had multiple subtypes within individuals, SA animals had far lower KoRV subtype diversity. Significantly different expression was observed for KoRV A,B,D,E and G variants between QLD and SA samples (unpaired t-test with unequal variance, P<0.05) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…A number of sequence variants of the env gene region, which encodes the surface unit (SU) of the envelope protein (Env), have also been identified (Figure 1). These vary between individuals and resemble the viral quasispecies common to infectious retroviruses 21 . There has been debate as to whether the KoRV B/J variant, which displays a different receptor usage to KoRV A, is an exogenous virus as it has been epidemiologically linked with clinical disease, however this is still unresolved 22 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Ishida, Zhao, Greenwood, and Roca (2015) estimated a maximum age for KoRV-A invasion of the koala germ line as 22,200-49,900 years ago, reflecting a lengthy association. Other subtypes are found with fewer copies and lower prevalence and can be geographically restricted in their distribution; these other subtypes appear to be primarily horizontally transmitted (Chappell et al, 2017).…”
Section: Chlamydial and Retroviral Infections In Koalasmentioning
confidence: 99%
“…Nine KoRV subtypes in three clades have thus far been described from wild or captive koala populations (Chappell et al., ). One of these, KoRV‐A, appears to be have been integrated into the genome of some koala populations (endogenized), and is found as multiple copies at 100% prevalence in some populations (Queensland and New South Wales) (Legione et al., ; Oliveira, Satija, Kouwenhoven, & Eiden, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of hybrid dysgenesis in Drosophila has provided insights into piRNA pathway adaptation to DNA transposon invasion in insects [16][17][18] , but the response to invasions of the mammalian genome has not been examined. KoRV-A is associated with leukemia, immunodeficiency and chlamydia infection in koala, and characterization of proviral integration led to the surprising discovery that the virus had entered the koala germline in the last 50,000 years and is spreading by an unusual combination of vertical and horizontal transfers 4,5,19,20 . The virus is believed to have entered the wild population at the northern end of Australia and swept south, where a few naive populations persist 5 .…”
mentioning
confidence: 99%